Pembelajaran Pendidikan Agama Islam Berbasis Saintific Untuk Anak Usia Dini - Nurkhima Nurhikma (Al-Bahtsu: Jurnal Penelitian Pendidikan Islam, 2022)
This research is motivated by the importance of learning Islamic Religious Education for early childhood as the initial basis for the introduction of Islamic values in children. In practice, Islamic Religious Education in PAUD or Kindergarten can be done in two ways, namely integrated into the six aspects of early childhood development or specifically in the form of Islamic Religious Education subjects which have their own time allocation and are taught by Islamic Religious Education teachers. Learning activities for early childhood can be done using a variety of interesting and fun methods, one of which is the scientific learning approach. Through this approach, early childhood will be invited to recognize and understand the material and values in Islamic Religious Education in a fun and scientific way. This scientific learning has several learning steps including observing, asking questions, gathering information, processing information, drawing conclusions, and communicating. This study discusses how scientific-based Islamic Religious Education learning for Early Childhood includes lesson plans, learning implementation, and learning evaluation. PAI learning planning for early childhood begins with preparing a Daily Learning Implementation Plan (RPPH) in which learning activities are arranged according to scientific learning steps and learning activities are adjusted to the stages of early childhood development. Furthermore, the implementation of learning is carried out in accordance with the Daily Learning Implementation Plan or RPPH that has been made. In the core learning activities, it is carried out by following the steps in scientific learning. Evaluation or assessment of learning on PAI learning content is carried out on 3 aspects, namely aspects of attitudes, knowledge, and skills. This assessment is carried out in accordance with the assessment plan that has been prepared in the RPPH. The assessment process is carried out as long as the child carries out activities starting from the initial activity to the closing activity. An assessment of the attitude spec can be made using anecdotal notes or attitude journals. Assessment of aspects of knowledge and skills can be done with the results of the work, observations, performance, or portfolio.